Uma modelagem para implementação de um APL - Arranjo Produtivo Local: o caso do setor metal mecânico da região sudoeste do estado do Paraná - Chiochetta, João Carlos (2005)
From the necessity to establish a program of regional development that seeks the integration of the industrial sector involving the segment of the metal mechanic area, was placed as a research problem: How arrive at a possible Local Productive Arrangement, from an accumulation of companies of the metal mechanic sector, installed in the Southwest region of the State of the Paraná? From of this indagation, the present work of research had for objective to elaborate a proposal of modeling of a Local Productive Arrangement - LPA - involving the metal mechanic sector, by means of a possible cooperative and interactive process, aiming at to the increase of the quality and of the productivity of the companies to make front to the competitiveness of the sector.